SISTEM INFORMASI PERSEDIAAN BARANG KONSUMSI BERBASIS WEB PADA K-STORE PRIMKOKAS KRAKATAU JUNCTION - masum masum; Hasan Hasan (Journal of Innovation And Future Technology (IFTECH), 2021)
K-store primkokas krakatau junction is cooperative serving members of consumer goods and general consumers, in the execution of his work still has many drawbacks one of which is in sector inventory often experience delays in delivery, the goods are not in accordance with demand, resulting in inventory warehouses often have a shortage of goods. Purpose of the Inventory Information System Web-Based Consumption In K-Store Primkokas Krakatau Junction to timely delivery of goods, the goods in accordance with the goods received in the request, as well as to meet the stocks held in warehouses. The method used in the Inventory Information System Web-Based In K-Store Primkokas Krakatau Junction is the waterfall method is a sequential software development process, in which progress is seen as flowing steadily downwards (like a waterfall) through the phases of planning, modeling, implementation (construction), and testing. Inventory Information System Web-Based Consumption In K-Store Primkokas Krakatau Junction is one alternative that will assist employees in their work, particularly in meeting the existing inventory in K-Store Primkokas Krakatau Junction.